2019
DOI: 10.3390/su11205789
|View full text |Cite
|
Sign up to set email alerts
|

Innovating with Limited Resources: The Antecedents and Consequences of Frugal Innovation

Abstract: Frugal innovation is a resource scarce solution for emerging market firms. Based upon the resource-constrained innovation perspective, this research theoretically explores and empirically examines the drivers and consequences of frugal innovation. The results of a firm-level survey show that two types of frugal innovation (cost innovation and affordable value innovation) positively affect the performance of emerging-market firms. We also address the issues of how emerging-market firms deal with institutional, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 95 publications
(208 reference statements)
1
51
0
1
Order By: Relevance
“…Through bricolage, knowledge generations enable organizations to break resource inertia and foster innovative creations (An et al, 2018; Ernst et al, 2015). Moreover, bricolage enables affordable and value‐added products with limited resources (Cai, Ying, Liu, & Wu, 2019). Through improvisation and experimental learning, firms with higher entrepreneurial bricolage are prone to devise low‐cost, value‐added products, and services for customers (Cai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Through bricolage, knowledge generations enable organizations to break resource inertia and foster innovative creations (An et al, 2018; Ernst et al, 2015). Moreover, bricolage enables affordable and value‐added products with limited resources (Cai, Ying, Liu, & Wu, 2019). Through improvisation and experimental learning, firms with higher entrepreneurial bricolage are prone to devise low‐cost, value‐added products, and services for customers (Cai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this period, 833 (40.87%) are set in the social context and address various issues, such as human resource management [81,82], organizational culture [79,83], social entrepreneurship [84,85], knowledge management [86], social learning [87], health care [88,89], social responsibility [77], education [90][91][92][93], and others. Around 26.7% of studies address the economic dimension in this period, highlighting the topics of performance [93][94][95], innovation [96,97], entrepreneurship [98], competitiveness [99,100], supply chains [101][102][103], and others. In the last decade, the environmental dimension (24.48%) reflects topics such as water management [104], sustainable policies [105][106][107], adaptation to climate change [108][109][110], eco-tourism [111,112], environmental responsibility [113,114], sustainable development [115][116][117], and the circular economy [118,119].…”
Section: Qualitative Content Analysismentioning
confidence: 99%
“…Some studies observed that structural rigidity could impede some firms from innovating for customers with quite different needs, which is a result of insufficient "Research and Development (R&D)" capabilities for building high-tech innovative products [36][37][38]. In view of this, some scholars have argued for frugal innovation, which is mainly focused on achieving dramatically lower costs to meet the expectations of resource-constrained consumers, with a secondary focus on providing functionalities and features that are adequate to meet specific needs [10]. According to Zeschky et al [39] and Wan et al [40], the main aim of this kind of innovation is to provide a very low price with adequate quality to serve resource-constrained customers.…”
Section: Sustainable Innovation Orientationmentioning
confidence: 99%
“…As a result of the dynamic and competitive nature that characterizes today's business environment [1], most companies have begun searching for an innovative business model as a strategy to achieve the objectives of their firm [2,3] with the aim of improving company performance [4,5], while some authors are of the opinion that this is for value creation [6,7]; Ballot et al [7] and Camison and Villar-Lopez [4] believe that this is for technology development and for the achievement and sustainability of competitive advantages [3,8]. In recent times, the issue of business model innovation (BMI) within the context of how firms innovate their ideas has gained tremendous attention from both academics and practitioners [1,9] and has also considered in regard to how to provide a solution to scarce resources, i.e., "frugal innovation" [10]. Meanwhile, over the time, the concept of BMI has been perceived from different dimensions among managers and researchers [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation